EMOTIONAL QUOTIENT AND THE SECOND YEAR STUDENTS’ SPEAKING ABILITY OF ENGLISH EDUCATION DEPARTMENT - Muhammad Syahruddin Nawir; Nur Aliyah Nur; Muhammad Wiranto (elstic : english language linguistics culture, 2021)
This study aims to find out the extent to which the significant correlation between emotional quotient and speaking ability on the second year students in the major of English Education Department. This research used multi-stage cluster sampling to gather data on 30 students from the total population of 101 students. The researchers used quantitative approach with correlation research design to reach the research objective. There were two instruments distributed to students namely USMEQ-i questionnaire for measuring students’ emotional quotient and Speaking Test for assessing students’ speaking ability. The findings showed that the score of students’ emotional quotient (2.85) was high emotional quotient by using USMEQ-i questionnaire and the score of students’ speaking ability (70.83) was fairly good speaking by using Speaking Test. Furthermore, the coefficient correlation (rxy) was 0.886. It indicated that the correlation was in high correlation. Based on the data above, the researchers conclude that the alternative hypothesis was accepted and null hypothesis was rejected. It means that there is a significant correlation between emotional quotient and speaking ability on second year students in the major of English Education Department. The researchers mention a suggestion to the teacher that emotional quotient should get serious attention to control, motivate, and regulate students’ emotional quotient. If students are able to control their emotions, they will get good grade in speaking activity. In addition, for the next researchers, they have to collect many new sources for analyzing and evaluating this study.